2009
DOI: 10.1091/mbc.e08-09-0909
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde Microtubule Transport Drives Microtubule Bending in LLC-PK1 Epithelial Cells

Abstract: Microtubules (MTs) have been proposed to act mechanically as compressive struts that resist both actomyosin contractile forces and their own polymerization forces to mechanically stabilize cell shape. To identify the origin of MT bending, we directly observed MT bending and F-actin transport dynamics in the periphery of LLC-PK1 epithelial cells. We found that F-actin is nearly stationary in these cells even as MTs are deformed, demonstrating that MT bending is not driven by actomyosin contractility. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
103
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 53 publications
16
103
0
Order By: Relevance
“…This is reminiscent of the curvatures that occur in gliding assays when microtubules are pinned by a dead motor. This analogy between gliding assays and in vivo microtubule bending has recently been explored using curvature distributions of microtubules located in the periphery of LLC-PK1 epithelial cells (Bicek et al 2007(Bicek et al , 2009) and in kinesin gliding assays. It was shown that microtubule curvature distributions in vivo and in vitro both exhibited an exponential decay, indicating the involvement of active forces.…”
Section: Resultsmentioning
confidence: 99%
“…This is reminiscent of the curvatures that occur in gliding assays when microtubules are pinned by a dead motor. This analogy between gliding assays and in vivo microtubule bending has recently been explored using curvature distributions of microtubules located in the periphery of LLC-PK1 epithelial cells (Bicek et al 2007(Bicek et al , 2009) and in kinesin gliding assays. It was shown that microtubule curvature distributions in vivo and in vitro both exhibited an exponential decay, indicating the involvement of active forces.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that the cause of microtubule buckling remains elusive, previous studies suggested mechanisms mediating microtubule bending and buckling. It has been shown that kinesin and dynein motors might result in microtubule buckling and breaking during telophase (Bicek et al, 2009). Because several microtubule motors are known to be necessary for the completion of cytokinesis (Zhu et al, 2005), perhaps these microtubule motors might also contribute to the central spindle buckling by either anchoring themselves to the PM or by anchoring to another microtubule to create a bending force.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubule sliding is central to the organization of the mitotic spindle and, here, might have a role in organelle partitioning during mitosis (see Goshima et al, 2005). The impact of motor force on microtubule structure would also have indirect consequences for any attached organelle (Bicek et al, 2009). A further example is provided by the attachment of the ER to microtubule tips, which results in the extension of the ER in response to microtubule polymerization (Grigoriev et al, 2008).…”
Section: Motors In Organelle Positioning and Signal Transductionmentioning
confidence: 99%